(untitled) (Computer systems and information technologies, 2023)
The modern development of service-oriented software systems is accompanied by the wide use of cloud technologies, which affect the competitiveness of companies and their systems, which provide opportunities to expand the client base thanks to the coverage of several regions of the city or country. The advantage of cloud services is availability in any part of the world where there is an Internet connection. Cloud providers provide a large volume of services for various needs: such as hosting, deployment of containers, file storage, databases, etc. In particular, all the most popular cloud providers offer several options for creating service-oriented software systems, including both standard technologies and proprietary developments. This paper compares the methods of creating service-oriented software systems based on the Azure cloud platform: Azure Container Apps, Azure Kubernete Service, and Azure Red Hat OpenShift. The subject area of technologies for the implementation of service-oriented application architecture is considered, and criteria for the analysis of methods for implementing applications with such an architecture are proposed. A software solution for comparing methods of creating service-oriented applications based on the Azure cloud platform was designed and developed. The developed software system provides an opportunity to rent scooters, bicycles and cars. The purpose of the study is a comparative analysis of the methods of creating service-oriented software systems based on Azure services, and the subject of the study is a software solution implemented using these methods. The purpose of this work will be the development of a software system that will provide an opportunity to rent scooters, bicycles and cars. Using this system, we will investigate the deployment of this system on certain services from Azure. The results of this research on Azure services: Azure Container Apps, Azure Kubernete Service and Azure Red Hat OpenShift can be used when creating a new software system, when expanding an existing software system, when transferring software system components from other platforms to the Azure platform using these services.